Istikhdām Ilqoo'i al-Mūfrodāt al-Yaūmiyyāh Fīī Ta’līīmi al-Insyā'i al-Kitābiy bīī Ma’hādy Mulazāmāh al-Hufadz Payakumbuh - Rosalina; Widayanti, Rizka; Bedra, Kddour Guettaoui (CV. Creative Tugu Pena, 2025)
Teaching composition at the Mulazamah Boarding School helped the process of reciting daily vocabulary because the difficulties and problems of teaching composition were the lack of vocabulary mastery among the students. The aims of this research are: to know the plan, to explain the process, and to demonstrate the evaluation of daily vocabulary delivery in teaching written composition at the Mulazamah Boarding School. This research is used as qualitative research, and the method for collecting its data is interviews, observation and documents. The sources of data for this research are the head of the institute, the school, and the students.As for the results of the research, in planning the daily vocabulary presentation, the supervisor chose the vocabulary presentation that would be given and presented it first to a professor from the Language Department in writing or an example of the useful sentence. So that the vocabulary provided is compatible with the need and appropriate in managing it. The vocabulary sources that will be provided are the Arabic Language Lessons Dictionary written by Abu Khuzayfa Ahmed bin Kadiat. As for the daily vocabulary recitation process, the supervisor gives two vocabulary words and two sentences for each vocabulary. The students made two other vocabulary sentences. The female students were divided into a small group, with the supervisor among them presenting the vocabulary. Vocabulary recitation took place four days a week, from Monday to Wednesday and on Saturday. As for evaluating daily vocabulary in teaching written composition at the Mulazamah Boarding School, it means in the form of practice questions. The learning process takes place, and of course, attendance and activity in asking questions when learning in class, answering questions, as well as evaluating the results during the exam. In the result of ninety-five there was one female student, in the result of ninety-four there was one female student, ninety-two female students, in ninety-one female students there was one, eighty-three female students, eighty-two female students, eighty one female student, in the result of seventy-nine there was one female student, and in the result of seventy-eight there was four Female students, seventy-five are two students, and as for the result of fifty-four, one student.So, this study expected to serve as a reference for educators, curriculum developers, and researchers in designing more effective and contextual vocabulary and writing learning.